Thermal Comfort and Adaptive Behaviour in a Naturally Ventilated Heritage School: A Field Study in a Tropical Highland Climate - Erica Bridgette; Etika Vidyarini; Andriyanto Wibisono (Green Publisher Indonesia, 2026)
Achieving thermal comfort in educational environments is crucial for student well-being, yet it poses a significant challenge for naturally ventilated heritage buildings in tropical climates. This study investigates the relationship between objective thermal conditions and subjective comfort perceptions in a colonial-era, naturally ventilated school in Bandung, Indonesia. A mixed-methods approach combined objective physical measurements (Ta, RH, Tg, WBGT) with subjective questionnaires (N=50) assessing thermal sensation, comfort, and adaptive behaviors. Findings reveal a significant disconnect between physical data and subjective experience. Counterintuitively, the objectively warmer classroom was perceived as more comfortable and less disruptive. Statistical analysis confirmed no significant correlation between thermal data and subjective responses (p > 0.05). Instead, higher occupant density and student physiology post-recess (thermal alliesthesia—the phenomenon where thermal perception is influenced by recent physiological changes) were more influential factors. The study concludes that a purely physical-metric approach is insufficient for heritage buildings, providing strong empirical support for the Adaptive Comfort Model. The research underscores that design and management strategies must consider contextual factors, such as occupant density and activity patterns, to effectively improve learning environments.